Win Some Lose Some? Evidence from a Randomized Microcredit Program Placement Experiment by Compartamos Banco - Manuela Angelucci; Dean S. Karlan; Jonathan Zinman (Institute for the Study of Labor (IZA), 2013)
Theory and evidence have raised concerns that microcredit does more harm than good, particularly when offered at high interest rates. We use a clustered randomized trial, and household surveys of eligible borrowers and their businesses, to estimate impacts from an expansion of group lending at 110% APR by the largest microlender in Mexico. Average effects on a rich set of outcomes measured 18-34 months post-expansion suggest some good and little harm. Other estimators identify heterogeneous treatment effects and effects on outcome distributions, but again yield little support for the hypothesis that microcredit causes harm.
Keywords: D12; D22; G21; O12; 330; microcredit; microcredit impact; microentrepreneurship; Compartamos Banco; Mikrofinanzierung; Kosten-Nutzen-Analyse; Mexiko